Strengthening Women’s Potentials and Capabilities: A Perceived Strategy to Narrow the Gender-Gap in Land Rights in South-Western Uganda - Prudence, Kemigisha (Advances in Social Sciences and Management, 2023)
The gender gap in land rights operates within the broader context of the bigger gender gap in society which is rooted deeply in informal/normative and formal/statutory structures. Security of tenure is a major determinant of the ability of women to improve the productivity of the land they use, to rebalance decision making power within the household, and to raise their status in the household, the community, and as citizens. There is thus the need of succinct strategies to narrow the gender gap in access to and control of the land because unequal access to land is one of the most important forms of economic inequality between men and women and has consequences for women’s capabilities as food producers and key contributors to human welfare. This study aimed at exploring the untapped potentials and capabilities of rural women that may be exploited to narrow the gender gap in land rights in Uganda. The study was conducted among the farmer groups and key informants in South Western Uganda. To narrow the gender gap in land rights, the study identified strategies for strengthening women’s potentials and capabilities that included formation of women’s groups, changing traditions and practices that discriminate against women in terms of land acquisition and land tenure security, increasing awareness and advocacy for women land rights, empowering them to obtain and defend their land rights and also to enhance their potential to utilize the existing legal legislations, legal aid and legal services.
Keywords: Women potentials; Women capabilities; Gender gap; Land rights